Penatalaksanaan Fisioterapi Pada Kasus Ischialgia Akibat Spondylosis Vertebra Lumbal 4-5 Di RSUD Saras Husada Purworejo - Bawono, Adicahyo, Totok Budi Santoso, S.Fis., MPH (2015)
Background: Scientific paper on case management physiotherapy ischialgia from spondylosis lumbar vertebrae 4-5 is intended to determine the management of physiotherapy, add insight and knowledge, and give rise to a variety of physical problems related to the lower back area and modalities that are given in this condition is SWD (shortwave diarthermy), TENS (Trancutaneus elektrical nerve stimulation) and exercise therapy (William Flexion exercise). Objective: restrictions that exist in a scientific paper aims to determine the effectiveness of the SWD (shortwave diarthermy), TENS (Trancutaneus elektrical nerve stimulation) and exercise therapy (William Flexion exercise) on the condition ischilgia from spondylosis lumbar vertebrae 4-5. In this case the treatment is done 6 times. Results: A decrease in the degree of pain where the pain still from T0 = very mild pain becomes T6 = no pain, tenderness of T0 = Pain is not so heavy into T6 = very mild pain, and painful motion of T0 = pain severe enough widened T6 = pain light. An increase in LGS in flexion and extension movements. The results obtained before treatment for flexion movements T0 = 8 cm and after treatment T6 = 13 cm, and for the extension motion before treated T0 = 3 cm and after treatment became T6 = 5cm. An increase in muscle strength of the trunk flexor T0 = 4 after treatment became T6 = 5. And an increase in functional capability. The results obtained when T0 = 17 before treatment and after treatment T6 = 15. Conclusion: further advice on scientific writing is more research needs to be conducted to determine what physiotherapy modalities berpengaruhdiantara modalities that have been applied to the above-mentioned conditions due spondylisis ischialgia vertebrae 4-5.